The Impact of Corporate Characteristics on Human Rights Disclosure: Construction Companies in Malaysia - Salawati, Sahari; Noradiva, Hamzah (The University of Chicago, 2014)
The need for a more holistic dimension of corporate operations on social interest has driven this study to explore the specific area of human rights reporting. Drawing upon institutional theory of organizations, we hypothesized that leverage, the presence of international operations and the government ownership influenced human rights disclosure (with size and profitability as control variables). Based on the data collected from the annual reports of construction firms in 2009, our findings reveals that the explanatory variables predicted in the hypothesis are not significantly related to the human rights disclosure. However, it was found that size to be significant regressors that help to explain the variability in the human rights disclosure. Our study contributes to regulators and standard setting bodies especially when evaluating corporate disclosure with regard on the specific issue of human rights.